2021
DOI: 10.1002/jobm.202100509
|View full text |Cite
|
Sign up to set email alerts
|

Propionic acid induces apoptosis‐like death in Escherichia coli O157

Abstract: Propionic acid (PPA), utilized in the manufacture of cellulose acetate propionate, is known to exhibit antimicrobial effects, but its mechanism in Escherichia coli O157 is still unknown. In general, antimicrobial activity is associated with reactive oxygen species (ROS), but ROS generation is not observed under PPA treatment. In addition to ROS, experiments were conducted to observe changes in trehalose and ion balance to discover factors that may affect the cell proliferation. Bacteria use trehalose, a sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Thus, the more concentrated they are in the growth medium, the more available they are to move into the cell; hence, the VFAs at 4 g/L were more effective against the tested bacterial strains. This agrees with Kim and Lee [17], who reported the dose-dependent nature of organic acids and also the complete inactivation of E. coli after 48 h of incubation when treated with 4 g/L of acetate, propionate and butyrate. Furthermore, the toxicity of VFAs is correlated with the pH of the growth medium (Figure S1), as also observed by Peh et al [38], because the ratio of the ionised form of VFA to the unionised form is influenced by pH.…”
Section: The Antibacterial Effect Of Vfas As a Function Of Concentrat...supporting
confidence: 92%
See 2 more Smart Citations
“…Thus, the more concentrated they are in the growth medium, the more available they are to move into the cell; hence, the VFAs at 4 g/L were more effective against the tested bacterial strains. This agrees with Kim and Lee [17], who reported the dose-dependent nature of organic acids and also the complete inactivation of E. coli after 48 h of incubation when treated with 4 g/L of acetate, propionate and butyrate. Furthermore, the toxicity of VFAs is correlated with the pH of the growth medium (Figure S1), as also observed by Peh et al [38], because the ratio of the ionised form of VFA to the unionised form is influenced by pH.…”
Section: The Antibacterial Effect Of Vfas As a Function Of Concentrat...supporting
confidence: 92%
“…Furthermore, Gomez-garcia et al [14] also observed that formic acid, which is also a low molecular weight VFA (C 1 ) with low pH, showed higher toxicity to Escherichia coli and Salmonella spp. Although propionic acid was comparatively the least effective VFA against all tested strains in this study, it is a potent antibacterial agent [17,50]. It achieved a significant reduction (>99%) in bacterial log CFUs at 4 g/L within the 48 h incubation period.…”
Section: Effect Of Carbon Chain Length On Vfas Toxicitymentioning
confidence: 68%
See 1 more Smart Citation
“…37 At the same time, it has antibacterial effect and can induce apoptosis-like death of Escherichia coli O157 cells. 38 These evidences indicate that the final fermentation product propionic acid of Muribaculaceae is closely related to the intestinal health and immunity of the host. Moreover, Muribaculaceae has also been reported to be associated with longevity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lactic acid (LA), the major metabolic end-product of lactobacilli [75], has been shown to sensitize Gram-negative E. coli to antimicrobials by disrupting the outer membrane of the target cells [76] or by interrupting an AHLmediated QS system [77]. Studies on propionic acid (PA), the main metabolic end-product of propionibacteria [19], have demonstrated that this short-chain fatty acid can be used alone or in combination with different organic acids or antibiotics to potentiate antibacterial or anti-biofilm effects [78][79][80][81]. Succinic acid (SA), a key intermediate metabolite of the tricarboxylic acid cycle, is also reported with antibacterial effects, e.g., against Cutibacterium acnes or with an ability to increase the antibiotic efficacy against P. aeruginosa PAO1 and alone to induce biofilm dispersal [82][83][84][85][86].…”
Section: Acetic and Propionic Acids Can Block The Induction Of Qs Of ...mentioning
confidence: 99%